Pengaruh Audit Internal dan Ketepatan Waktu Pelaporan Keuangan terhadap Integritas Laporan Keuangan pada Perusahaan Sektor Teknologi yang Terdaftar di BEI 2021-2024 - Alfred Wijaya; Mutiara Maimunah (AKUNTANSI 45, 2026)
This study aims to analyze the influence of internal audit and the timeliness of financial reporting on the integrity of financial statements, focusing on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study employed a quantitative approach using secondary data collected from annual reports and financial statements published by the companies. The population consisted of all manufacturing companies listed on the IDX, while the sampling technique used was purposive sampling based on predetermined criteria. As a result, 21 companies were selected, producing a total of 84 research samples. The analytical method applied in this research was multiple linear regression analysis to examine the relationship between the independent variables and the integrity of financial statements. The findings indicate that internal audit has a negative effect on the integrity of financial statements, suggesting that the implementation of internal audit in the observed companies has not been fully effective in improving the reliability and transparency of financial reporting. Meanwhile, the timeliness of financial reporting was found to have no significant effect on the integrity of financial statements. These results imply that timely reporting alone is insufficient to guarantee high-quality and trustworthy financial statements without stronger internal control mechanisms and effective corporate governance practices.